Spiritual competency in psychotherapy - Brownell, Philip (Clinical psychologist) (New York : Springer Publishing Company, 2015)
Historically, mental health clinicians were trained to refer clients' spiritual issues to pastoral professionals. However, the current requirement for competence with diverse cultural concerns in counseling and psychotherapy may include those of a religious nature. Using a nonsectarian approach that can complement a wide range of psychotherapeutic orientations, this practical guide helps therapists and counselors gain competence in working with clients who are dealing with spiritual issues in their lives. Written by an experienced clinical psychologist who is also an ordained clergyman, the bo.
Chapter 12: Faith and UncertaintyWhat to Do; Chapter 13: Communal Belonging; What to Do; Chapter 14: Dissatisfaction With God; What to Do; Chapter 15: Rigidity and Legalism; What to Do?; Chapter 16: Abuse; Abuse in Religious Community; Abuse of Religious Community; What to Do; Chapter 17: Spiritism, Spiritualism, and the Occult; What to Do?; Notes; Chapter 18: Endings, Death, and Personal Eschatology; What to Do; Notes; Conclusion.
Includes bibliographical references and index.
Print version record. Print version is xx, 248 pages.
Master record variable field(s) change: 650
Keywords: Psychology and religion; Psychology; Psychotherapy; Religion; Spirituality; Psychotherapy; Religion and Psychology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Psychology and religion; Psychology; Psychotherapy; Religion; Electronic books; Handbooks and manuals